On the question of the features and effectiveness of police supervision in the provinces of the Russian empire in the second half of the XIX century - M. L. Radchenko; I. S. Efremova (Вестник Самарского университета: История, педагогика, филология)
The article focuses on the question of the organization of police supervision in the Russian Empire, its types, features of application and, most importantly, the effectiveness and likelihood of using public and secret police supervision to minimize the number of politically «dangerous» elements that increased in Russian society in the second half of the XIX century. The attached archival materials make it possible to clearly show the level of organization of supervision and note the features of the organization in the provinces of measures to ensure control over the implementation of the «Regulations on Police Supervision». Maintaining special register books, collecting data, establishing regular public and secret surveillance, viewing correspondence and other preventive measures were supposed to ensure the effectiveness of the implementation of tasks to ensure the protection of order in the Empire.